Brand Building in the Era of Mobility and Emergence of ’New Imagined Communities’: A Conceptual Analysis - Kandpal, Anshul; Patra, Santosh K. (Indian Journal of Marketing, 2013)
This is a conceptual paper and is an attempt to explore the transitional effect of brand building in the new era of mobiles and the Internet. Transition and mobility have been the laws of nature and have been witnessed from time immemorial. However, the current and future generations are going to witness a transformation which redefines the idea of space and geographical territory. The prime mover of this transformation will be new media. To understand this transition well and to be in sync with the nuances of mobility will be crucial to organizational success in the 21st century. In this paper, we have discussed how organizations can form brand communities on the lines of Benedict Anderson’s ’Imagined Communities’. The paper also highlights the fact that the phenomenon of mobility seen today is not just a consequence of an information explosion, but is also a result of the nature of new media (the Internet and mobile) and its impact on social constructs.